Using G-Suite Docs to Improve Students’ Writing Ability at SMA Negeri 1 Batuan, Sumenep - Norani Yanuar Subandi; Hablil Warid; Sulistyaningsih (STKIP PGRI SIDOARJO, 2021)
The aim of this research were to describe the implementation of Using G - Suite Docs to Improve Students’ Writing Ability at SMA Negeri 1 Batuan, Sumenep and to find out the achievement of student’s writing ability in Using G - Suite at SMA Negeri 1 Batuan, Sumenep. The approach used in this research was classroom action research. Data collection tools in this study were observation sheets of learning management through G-Suite Docs media, student activity observation sheets and tests. The objects of this study were 25 students of class XII IPA 1 SMA Negeri 1 Batuan even semester of the 2020/2021 school year. The research showed that the result of implementing of using G-Suite Docs showed that the students were more enthusiastic in writing discussion text and all students could respond to their group work by commenting on the process in writing. Moreover, the students achievement from the initial conditions up to second cycle. The average of initial condition was 66.6 changed to be 79.64 or increased 80% with the result of completeness reaching 92%. Keywords: G - Suite Docs, Writing ability, Discussion Text